Sistem Pendukung Keputusan Menentukan Penerimaan Beasiswa Model Fuzzy Multiple Attribute Decision Making - Nawawi, Imam (LPPM STMIK ANTAR BANGSA, 2018)
AbstractÃ¢â‚¬â€In every education institutions especially schools, a lot of scholarships are aimed at students, both achievers and disadvantaged. This scholarship is intended to help alleviate the burden of the cost of students who get them in taking their studies. To help determine in determining a person eligible to receive the scholarship, it takes a decision support system. In the process of development of a decision support system to determine the scholarship recipients with the criteria that have been established, such as the number of parents income, number of dependents of parents, number of siblings, the average value, and the percentage of attendance of students is using Fuzzy Multiple Attribute Decision Making (FMADM). FMADM is a method used to find the optimal alternative of a number of alternatives with certain criteria. Research carried out by finding the weight values for each attribute, then carried rating process that will determine the optimal alternative, that the best students. Based on test result, a system built to help the team work of scholarship selectors in making the selection of scholarship, can accelerate the scholarship selection process, can reduce errors in determining the scholarship recipients, and can facilitate team selectors in determining who will receive a scholarship to the right.Ã‚Â IntisariÃ¢â‚¬â€Di setiap lembaga pendidikan khususnya sekolah, banyak sekali beasiswa yang ditujukan kepada siswa, baik yang berprestasi maupun yang kurang mampu. Beasiswa ditujukan untuk membantu meringankan beban biaya siswa yang mendapatkannya dalam menempuh studinya. Untuk membantu penentuan dalam menetapkan seseorang yang layak menerima beasiswa, maka dibutuhkan sebuah sistem pendukung keputusan. Dalam proses pembangunan system pendukung keputusan untuk menentukan penerima beasiswa dengan kriteria-kriteria yang telah ditetapkan, seperti jumlah penghasilan orang tua, jumlah tanggungan orang tua, jumlah saudara kandung, nilai rata-rata, dan persentase kehadiran siswa (kerajinan) yaitu menggunakan metode Fuzzy Multiple Attribute Decision Making (FMADM). FMADM adalah suatu metode yang digunakan untuk mencari alternatif optimal dari sejumlah alternatif dengan kriteria tertentu, penelitian dilakukan dengan mencari nilai bobot untuk setiap atribut, kemudian dilakukan proses perangkingan yang akan menentukan alternative yang optimal, yaitu siswa terbaik. Berdasarkan hasil pengujian, sistem yang dibangun dapat membantu kerja tim penyeleksi beasiswa dalam melakukan penyeleksian beasiswa, dapat mempercepat proses penyeleksian beasiswa, dapat mengurangi kesalahan dalam menentukan penerima beasiswa, dan dapat mempermudah tim penyeleksi dalam menentukan siapa yang akan menerima beasiswa dengan tepat.Ã‚Â Kata kunci: penentuan penerima beasiswa, kriteria, bobot, SPK, FMADM